The Impacts of a Financial Structure on Performances - Pestonji, Chosita (Hatyai Academic Journal, 2023)
The purpose of this study was to determine 1) the impacts of a financial structure on profitability and firm value, and 2) the impact of profitability on firm value within the property and construction segment in the Stock Exchange of Thailand (SET). The data, mostly secondary, were derived from the financial statements before and during the COVID-19 pandemic periods. The outcomes show that the application of a conservative working capital financing policy increased the firm value during the pandemic. In addition, a capital structure based on the pecking order theory is also subsequently associated with increasing profitability both before and during the pandemic periods, which reflects the potential risk of leverage to investors’ stances. Finally, having high profitability also deliberately elevated the firm value both before and during the pandemic.